2006
DOI: 10.1200/jco.2005.03.2235
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Long-Term Follow-Up for Early-Stage Breast Cancer: A Comparison of Family Physician Versus Specialist Care

Abstract: Breast cancer patients can be offered follow-up by their family physician without concern that important recurrence-related SCEs will occur more frequently or that HRQL will be negatively affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
385
2
21

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(418 citation statements)
references
References 54 publications
10
385
2
21
Order By: Relevance
“…Quality of life tools have been used to assess the impact of novel follow-up methods previously (Grunfeld et al, 1996(Grunfeld et al, , 2006Brown et al, 2002;Koinberg et al, 2004), but never specifically to screen for problems. Using such tools in this way should be done with care.…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life tools have been used to assess the impact of novel follow-up methods previously (Grunfeld et al, 1996(Grunfeld et al, , 2006Brown et al, 2002;Koinberg et al, 2004), but never specifically to screen for problems. Using such tools in this way should be done with care.…”
Section: Discussionmentioning
confidence: 99%
“…The three published RCTs examined follow-up for breast cancer 3,27 and colon cancer 30 (Table 1, part a). One of the breast cancer studies was a non-inferiority trial, 27 and the other incorporated a cost analysis.…”
Section: Primary Versus Secondary Carementioning
confidence: 99%
“…Five studies compared primary versus secondary care follow-up, 3,[27][28][29][30] but two were only reported in abstract form (a non-randomised study of patients who had undergone haematopoietic stem cell transplantation for malignant haematologic disorders 28 and a randomised controlled trial [RCT] of patients with cutaneous melanoma 29 ). The three published RCTs examined follow-up for breast cancer 3,27 and colon cancer 30 (Table 1, part a).…”
Section: Primary Versus Secondary Carementioning
confidence: 99%
“…A recent study in Canada found that family physicians are able to monitor breast cancer patients for recurrence-related serious clinical events as well as cancer specialists, 9 suggesting that PCPs can take on the role of monitoring survivors for recurrence while providing ongoing preventive and primary care services. In contrast, whereas medical oncologists may provide some primary care services to patients, particularly during the active treatment phase, they prefer to spend their time on cancer-directed care.…”
Section: Introductionmentioning
confidence: 99%